(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The introduction into Italy of Rhizoecus saintpauliae Williams is reported. The species was collected on the roots of bonsai plants imported from Japan. An identification key is provided to separate the commonest greenhouse species of Rhizoecus.